2012
DOI: 10.2298/vsp1206492v
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of amplitude-integrated electroencephalography in neonates with hypoxic-ischemic encephalopathy

Abstract: Our results confirm that aEEG is simple and accurate bedside diagnostic method for assessing extension of hypoxic-ischemic brain damage and early identification of neonates with perinatal HIE who are at high risk of neurodevelopmental impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…In comparison, electroclinical dissociation has been reported to occur up to 28% of neonates with HIE; however this figure was based on aEEG findings in neonates above 32 weeks gestation and its association with anticonvulsant administration was not described. [20] The studies by van Rooij et al [7] and Mercuri et al [8] did not provide information on the dissociation of seizures. Many of the previous studies reported the clinical response to anticonvulsants without any EEG monitoring.…”
Section: Discussionmentioning
confidence: 98%
“…In comparison, electroclinical dissociation has been reported to occur up to 28% of neonates with HIE; however this figure was based on aEEG findings in neonates above 32 weeks gestation and its association with anticonvulsant administration was not described. [20] The studies by van Rooij et al [7] and Mercuri et al [8] did not provide information on the dissociation of seizures. Many of the previous studies reported the clinical response to anticonvulsants without any EEG monitoring.…”
Section: Discussionmentioning
confidence: 98%
“…In infants who continued to have severely abnormal EEG findings, death, spastic quadriplegia, and major developmental delay were observed. 38,39 There have been conflicting reports regarding EEG findings in outcome prediction. 15,16 Studies suggest that EEG can be a useful predictor of outcome in severe HIE injuries, but that it is not a strong predictor of developmental outcome in mild-to-moderate cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic ischemic encephalopathy depending on severity yields the most abnormal results with 66.66% background activity suppression for HIE-III 5 . Recently Vasiljevic B et al confirm that a EEG is simple and accurate bedside diagnostic method for assessing extension of hypoxic-ischemic brain damage and early identification of neonates with perinatal HIE who are at high risk of neurodevelopmental impairment 7 .…”
mentioning
confidence: 99%